Sistem Pengurusan Futsal City Nine: Futsal City Nine Management System - AB. LLAH, MUHAMMAD ANAS; MOHD. YASIN, SUHAILA (Applied Information Technology And Computer Science, 2022)
City Nine Futsal Management System is a web-based system that act as a medium to manage court bookings and sports equipment inventory data. Futsal City Nine faces a problem where the current system of managing customer order data and inventory records of futsal equipment uses only paper and pen. Due to that, Futsal City Nine is likely to experience a high risk of duplication and loss of booking and sports equipment inventory data. Therefore, this management system is specially developed for Futsal City Nine’s customers and management to overcome this problem. This system is designed using the structured approach and is accessed online. The model used in the development of this system is the Prototype Model. Sublime is used to develop the software, with Xampp as the web server solution. Finally, it is expected that the Futsal City Nine Management System will be able to benefit Futsal City Nine’s customers and the management in obtaining information, performing the booking process, systematically recording the sports equipment and obtaining the related futsal court’s feedback.